Ser humano, animal y animalidad. Novedad y alcance de los Conceptos fundamentales de la metafísica. Mundo, Finitud, soledad 1929/30 de Martin Heidegger - Muñoz Pérez, Enrique (Veritas, 2013)
The aim of this paper is to show the shift that occurs in Heidegger's thought in relation to the concepts of «human being», «animal» and «animañty» companng, first, his treatment of the themes in "Being and Lime" (1927) and "The Lundamental Concepts of Metaphysics. World, Linitude, Solitude" (1929-1930). Secondly, I explore tendencies in the discussion of animality in Heideggerian interpretations today Lhe guiding question of our work is why does Heidegger rehabilítate the concept of «human being», «animal» and «animañty» in "The Lundamental Concepts of Metaphysics. World, Linitude, Solitude?" Lhis question alhws us to discuss some of the current interpretations of this problem.